Research Progress in Nanopharmaceuticals with Different Delivery Routes in the Antivirus Field - Shi, Yenong; He, Dongqiong; Zhang, Xianwei; Yuan, Mingqing; Liu, Xu (Current Pharmaceutical Design, 2023)
Human health is significantly threatened by infectious diseases caused by viral infection. Over the years, there have been numerous virus epidemics worldwide, causing millions of deaths. Traditional antiviral medications have many problems, including poor solubility and antiviral resistance. Additionally, because different drug delivery methods have different biological barriers to overcome, the drug’s bioavailability will be significantly affected. Therefore, it is essential that researchers create more effective antiviral drugs. To serve as a guide for the future development of nanosized antiviral drugs with stronger and more precise therapeutic effects, research has been performed on nanotechnology in the field of antiviral therapy. This review summarizes the recent developments in antiviral nanopharmaceuticals with different delivery routes. Research on 7 typical viruses, including COVID-19, has been included in this review. After being loaded into nanoparticles, antiviral drugs can be delivered through several drug modes of delivery, overcoming biological barriers. Moreover, some nanoparticles themselves have the ability to combat infections, so they can be used in conjunction with antiviral medication. The use of nanoparticle medications through various routes of administration can result in their unique benefits. They can be capable of overcoming its limitations as well as retaining the advantages of this method of delivery. This will motivate researchers to conducted a new investigation on nanoparticle medicines from the standpoint of the route of administration in order to increase the practicability of antiviral medications.
Keywords: antiviral drugs